Design and modeling of a novel compact solar collector with phase change material - Osman, Mohamed (AUC Knowledge Fountain, 2020)
The potential of integrating phase change materials (PCM) directly to solar collectors is proposed as a promising innovative modification for solar collectors in recent years. Accordingly, several compact PCM-collector designs are presented and compared to the conventional solar collector systems. In this study, a single vacuum tube is experimentally tested as a building block of the novel evacuated tube collector-storage solar water heater (ETCS). The free space of a single evacuated tube with a U-bend copper pipe is filled with Paraffin wax as a PCM, while water is used as heat transfer fluid (HTF). In addition, a longitudinal aluminum fin is used to enhance the heat transfer between the copper tube and the PCM. The performance of the proposed building blocks is evaluated under several charging and discharging experiments at different operating conditions. The tested tubes are evaluated in terms of cumulative recovered energy, energy storage/recovery efficiency, effectiveness, and charging-discharging cycle time. The results show that natural convection is the dominating heat transfer mode for 65% of the charging time. For the finned tube, the results show that increasing the PCM initial temperature from 65℃ to 80℃, increases the recovered energy and the total energy efficiency by 19% and 24%, respectively. For the un-finned tube, such an increase in PCM initial temperature increases the recovered energy and total energy efficiency by 5% and 9%, respectively. On the other hand, increasing the flow rate of the HTF from 0.3 l/min to 0.5 l/min decreases the effectiveness to 18% and 11% for the finned and un-finned tube, respectively. The heat loss test shows that the heat retention of the finned and un-finned tube after 12 hours test is almost similar at 34% and 32%, respectively. Further, the experimental results are used to validate a numerical model that is used to investigate the effect of tube design on thermal performance. Moreover, the effective heat capacity method is used to model the proposed building block, and the model is validated using both the experimental and numerical results. In addition, a simplified 2-D model is developed and used for investigating tube performance with different design parameters. Finally, the simplified model is integrated with a design methodology that is developed to be used as a designing tool for novel ETCS systems. The methodology presented in this study is used to design a new generation of solar collectors that work as a stand-alone compact solar water heater for heat demand in the night.